Waste Derived Biocomposite for Simultaneous Biosorption of Organic Matter and Nutrients from Green Straw Biorefinery Effluent in Continuous Mode Activated Sludge Systems - Jagaba A.H.; Kutty S.R.M.; Baloo L.; Hayder G.; Birniwa A.H.; Taha A.T.B.; Mnzool M.; Lawal I.M. (MDPI, 2023)
The conventional disposal of green straws through burning can be eliminated in a biorefinery that converts them into a range of sustainable commercial products. However, this leads to the generation of green straw biorefinery effluent (GSBE). Green straw biorefineries discharge wastewater into the ecosystem that contains high concentrations of COD and NH4+?N. It is one of the most notable sources of visual pollution and disruption of aquatic life as well as public health that requires treatment prior to discharge. To improve the GSBE quality for environmental sustainability, the attainment of sustainable development goals 6, 9, and 14, clean water and sanitation, inorganic and organic waste utilization for added values from material, and life below water is very important. Therefore, the effectiveness of the continuous mode activated sludge (CMAS) system and the biocomposite-basedcontinuous mode activated sludge (SB-CMAS) system in the treatment of GSBE was investigated in this study. Response surface methodology (RSM) was used to optimize the process variables. At their optimized conditions, the performances of CMAS and SB-CMAS were analyzed in terms of COD and NH4+?N. Findings showed 81.21% and 95.50% COD and 78.31% and 87.34% NH4+?N reduction in concentration for CMAS and SB-CMAS, respectively. The high COD and NH4+?N removal efficiencies indicate the better performance of CMAS and SB-CMAS. The first- and second-order models and the modified StoverKincannon biokinetic models were utilized to analyze substrate removal rates. It was discovered that the modified Stover models were ideal for the measured data with R2 values 0.99646 and 0.91236 attained for COD and NH4+?N, respectively, in CMAS. The SB-CMAS had 0.99932 and 0.99533 for COD and NH4+?N, respectively. Maximum contaminant elimination was attained at 60% GSBE and 2-day HRT. Thus, to achieve the UN SDGs for 2030, findings from this study have the potential to answer goals 6, 9, and 14. 2022 by the authors.